2022
DOI: 10.1039/d2nj02634a
|View full text |Cite
|
Sign up to set email alerts
|

A simple overview of toxicity of ionic liquids and designs of biocompatible ionic liquids

Abstract: Evaluation of toxicity of ionic liquids has been less prioritized, compared to the development of new ionic liquids and their applications. Focus on the toxicity of ionic liquids should be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 94 publications
2
20
0
Order By: Relevance
“…C) Aromatic moieties of EXLX1 interacting with cellotetraose by hydrophobic interactions (PDB; 4FG2). [20] [29] applicable to the cell wall in living cells, ILs completely comprised of bioderived ions (i. e., choline cation, amino acid anion) were developed and presented less toxicity than imidazolium-based ILs. [27] Kuroda et al designed ZILs as cell wall dissociating solvents and dramatically improved the cytotoxicity of ILs.…”
Section: Cellulose-loosening Low Molecular-weight Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…C) Aromatic moieties of EXLX1 interacting with cellotetraose by hydrophobic interactions (PDB; 4FG2). [20] [29] applicable to the cell wall in living cells, ILs completely comprised of bioderived ions (i. e., choline cation, amino acid anion) were developed and presented less toxicity than imidazolium-based ILs. [27] Kuroda et al designed ZILs as cell wall dissociating solvents and dramatically improved the cytotoxicity of ILs.…”
Section: Cellulose-loosening Low Molecular-weight Moleculesmentioning
confidence: 99%
“…[28] Introducing anion moieties (i. e., carboxylate and sulfonate) at the terminus of alkyl chains that were covalently linked with the imidazolium cation successfully suppressed the alkyl chains from piercing the cell membrane by hydrophobic interactions and selectively dissociated cellulose fibrils in the cell wall of microbes (Figure 4C). [29] In particular, OE 2 imC 3 C, a ZIL, which is liquid under a mild temperature, showed great biomembrane compatibility (EC 50 = 158 g L À 1 ), improving cell viability by 6 times compared to that of a common cellulose-dissolving solvent (LiCl/N,Ndimethylacetamide) to achieve the growth of recombinant Escherichia coli. This novel cell wall-loosening ZIL has potential applications in various fields, especially plant gene modification.…”
Section: Cellulose-loosening Low Molecular-weight Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HCl or HF is released when anions containing Cl or F hydrolyze, which is also harmful to the environment . When these ionic liquids are discharged through wastewater after application, they can also pose an environmental hazard, which is contrary to the original intention of ionic liquids as environmentally friendly solvents . Therefore, in recent years, people are more interested in using biocompatible materials to produce nontoxic and environmentally friendly ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…, ILs have always been a research hotspot in recent years. 20–22 It's revealed that the enzyme toxicity of imidazolium-based ILs have a close relationship with their structure, such as the type of anions and the length of alkyl chain. 23 For example, the inhibitory effect of anions of N -methylimidazolium-based ILs on lactic dehydrogenase enzyme follows the order: CF 3 SO 3 − > BF 4 − > Br − > Cl − , and the longer the alkylated side chain, the severer the inhibition.…”
Section: Introductionmentioning
confidence: 99%